The Translation of Malay Song Lyric in Upin & Ipin: The Lone Gibbon Kris Film: Language and Cultural Similarity - Nur Afifah Atirah, Saperi; Roslan, Ali; Mohamad Fairuz, Ali (2022)
This study aims to investigate language and cultural similarities in English subtitles of a Malay song lyric from a well-known local animated film, Upin & Ipin: The Lone Gibbon Kris. The Malay culture portrayed in the source language (Malay) which is translated into the target language (English), may not be understood or misinterpreted by the target audiences if the translation is not correctly translated. In this study, a qualitative descriptive method is applied. The research instrument is a selected Malay song lyric in Upin & Ipin: The Lone Gibbon Kris film from the Netflix platform, namely “Keris Sakti” along with its English subtitles, which are extracted and analyzed comprehensively. Moreover, the procedure of this study comprises data collection, comparing data, and evaluating Malay culture translation. This study found that the translation of the target language (English) has many inaccuracies from the source language (Malay). This is due to the fact that cultural differences are the main factor that contributes to misunderstandings and misinterpretations of meaning. Hence, accurate translation is worthy of attention especially when the film is on the global stage, yet the translations from the selected Malay song lyric in Upin & Ipin: The Lone Gibbon Kris film is very significant to expose the richness of Malay culture as well as offer a new perspective in the eyes of the Western world.